Coverage and predictors of the uptake of the mass drug administration of praziquantel chemotherapy for schistosomiasis in a selected urban setting in Zambia - Kiesolo, Felix Nzonzi; Sampa, Mutale; Moonga, Given; Michelo, Charles; Jacobs, Choolwe (Frontiers in Epidemiology, 2023)
The burden of schistosomiasis in Zambia has remained high over the years. The World Health Assembly recommended adequate mass drug administration coverage for schistosomiasis using Praziquantel chemotherapy for school-aged children and all at-risks adults. We aimed at investigating the coverage and the factors associated to the uptake for MDA for schistosomiasis in Ng’ombe compound of Lusaka, Zambia. A cross-sectional survey was conducted in May and June 2021 via phone calls to the residents of Ng’ombe compound. Commcare software was used in the conduct of the survey. Pearson’s Chi-square test and multiple logistic regression were conducted using the STATA version 15.0. 769 study participants were randomly selected using systematic sampling, of which 76.3% were younger than 40 years, 64.9% were female, 64.4% were married, 56.3% had reached the secondary educational level and 51.9% were employed. Coverage for MDA for schistosomiasis in Ng’ombe compound in 2018 was found to be 49.8% (95% CI: 46.2% - 53.4%). Positive predictors of the MDA were prior knowledge of the occurrence of the MDA in 2018 (aOR: 2.892, p<0.001) and believing that the provision of snacks was important during the MDA with PZQ in Ng’ombe compound (aOR: 1.926, p=0.001), whereas age (aOR:0.979, p=0.009), marital status (aOR:0.620, p=0.006), employment status (aOR:0.587, p=0.001) were negative predictors of the MDA. Elimination of the burden of schistosomiasis in endemic settings needs the attainment of an optimum coverage and uptake during MDA with PZQ. Therefore, prior knowledge about an impending intervention and the provision of snacks or foods during the intervention should be prioritized by MDA implementers, while background characteristics such as age, marital status, and employment status need to be taken into consideration when planning and promoting uptake in future MDAs.